Swelling Degree of Carrageenan-Corncob Bead Gel in Various Media - Sperisa Distantina; Mujtahid Kaavessina; Saktika Rofi'ah Haryani; Rif'ah Ulfatun Hasanah (CHEMICA: Jurnal Teknik Kimia, 2021)
Bead hydrogels were prepared from carrageenan-corncob mixture by physically and chemically crosslinking. The aims are to investigate the effect of carrageenan-corncob weight ratio and glutaraldehyde crosslinking on the swelling degree properties. The mixture of various carrageenan-corncob weight ratio (1:2, 1:1, 2:1, and 1:0) was dropped into KCl and CaCl2 solution and then the obtained bead gels was dried. The dried bead gel was crosslinked using glutaraldehyde 4%. The swelling degree behavior of the bead gels were tested in distilled water, 0.1M NaCl, and synthetic urine. The bead gels based on the mixture of carrageenan-corncob exhibited the hydrogel property. The highest swelling degree is carrageenan-corncob bead gels in the ratio of 1:0. The highest swelling degree is found in the distilled water and the lowest is in the synthetic urine. The 4% glutaraldehyde crosslinking does not show specific different results for carrageenan-corncob bead gels.